Implementasi Projek Penguatan Profil Pelajar Pancasila Dalam Pengembangan Karakter Peserta Didik di SMP N 3 Kertek Wonosobo - Elsa Lestari; KH. Ahmad Zuhdi; Hidayatu Munawaroh (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This thesis aims to: 1) Understand the concept of the Pancasila Student Profile Strengthening Project in developing the character of students at SMP N 3 Kertek Wonosobo; 2) Knowing the implementation of the Pancasila Student Profile Strengthening Project in developing the character of students at SMP N 3 Kertek Wonosobo; 3) Knowing the supporting and inhibiting factors in the implementation of the Strengthening Pancasila Student Profile Project in developing the character of students at SMP N 3 Kertek Wonosobo.This research uses a qualitative type of research using a descriptive approach to collect in-depth information from relevant sources such as teachers, school principals and students through interviews, observations and documentation. After the data is collected, it is then analyzed using data analysis, namely, data reduction, data presentation, and conclusions.The research results show that: 1) The concept of the Pancasila Student Profile Strengthening Project used at SMP N 3 Kertek Wonosobo is in accordance with the design expected by the Ministry of Education and Culture, where the aim is to motivate students to contribute more to the surrounding environment. The concept prepared includes several stages, including forming a coordinator and facilitator team, selecting character dimensions to be developed, selecting themes and activity topics, allocating time, and creating modules. 2) The implementation of the Project for Strengthening the Pancasila Student Profile in developing the character of students at SMP N 3 Kertek Wonosobo has been successfully carried out through three stages, namely the inspiration stage, the creation stage and the dedication stage. Through the project implementation process, character development is embedded in accordance with the dimensions of the Pancasila student profile. 3) Supporting factors for the Strengthening Pancasila Student Profile Project in developing the character of students at SMP N 3 Kertek Wonosobo include choosing a theme that is appropriate to the school environment, the availability of facilities and infrastructure, and collaboration between students, teachers and the community. The inhibiting factors are budget limitations, lack of student readiness, and less effective technical distribution of picket teacher facilitators.